FIRST ROOTED, THEN GROUNDED: THE POSITION OF THE CHURCH INSTITUTION IN KUYPER’S ECCLESIOLOGY - Surya Harefa (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2020)
This article revisits the position of the institutional church in the ecclesiology of Abraham Kuyper (1837—1920). Following the growing interest in the life and work of Kuyper in North America, some scholars pay attention to the importance of his ecclesiology. However, it is common to consider that Kuyper in his later life preferred the aspect of the church as organism and thus marginalizing the church as institution. After exploring his ecclesiological concept on the distinction of the church as organism and institution, this paper examines several major works of Kuyper on the institutional church written in his later life. Finding that Kuyper consistently viewed the institutional church highly, I argue that his restriction toward the church as insitution is to strengthen and provide a stable position of the institutional church in modern society. KEYWORDS: Kuyper, church as institution, church as organism, public theology